Tanggung Jawab Hukum Praktik Tanpa Surat Izin oleh Penata Anestesi di Rumah Sakit (Studi di Rumah Sakit Umum Daerah Sangatta) - Edi Prayitno (Jurnal Hukum dan Etika Kesehatan, 2021)
Health jurisdiction is growing up nowadays. Juridically, hospital takes over all the charge of negligence caused by health workers in the hospital. As the preventive, the hospital did credential to all health workers that do the direct medical treatment, one of them is ownership of the license. There are law issues in hospital’s services, such as practice without a license that are done by anesthesia directors. It causes legality problems and burdens charge from practice without license that are did by anesthesia director in hospital. The research method is normative juridical, using statute approach and conceptual approach. The result of research obtains that hospital does not take the charge and take the responsibilities legally about the practice without a license that are done by anesthesia director, depends on agreement letter between hospital and anesthesia director. So that respondeat superior doctrine that implied in article 46 Law Number 44 Year 2009 concerning to The Hospital, do not apply absolutely.